2008
DOI: 10.1111/j.1742-7843.2008.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Doses of Thalidomide in Experimentally Induced Inflammatory Bowel Disease in Rats

Abstract: The present study was carried out to evaluate the effect of different doses of thalidomide in experimentally induced inflammatory bowel disease in rats. Adult Wistar rats of either sex were used (n = 36). Colitis was induced by a single intra-colonic application of 20 mg 2,4,6-trinitrobenzene sulfonic acid (TNBS) dissolved in 35% ethanol into the descending colon. Rats were divided into six groups (n = 6). Animals were treated with vehicle (ethanol), TNBS dissolved in 35% ethanol, thalidomide (with different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In present study, treatment with endostatin in a dose which had anti-angiogenic and anti-tumor effects in vivo (Folkman, 2006) significantly improved clinical and histologic signs of DSS-induced UC in MMP-9 KO mice. These results are supported by other studies showing that the potent inhibitor of angiogenesis thalidomide attenuates IBD in patients (Plamondon et al, 2007;Vasiliauskas et al, 1999) and in animal models (Prakash et al, 2008). Furthermore, deletion of thrombospondin-1 in mice, which is upregulated by endostatin (Abdollahi et al, 2004), evoked more severe experimental UC vs. WT mice (Punekar et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
“…In present study, treatment with endostatin in a dose which had anti-angiogenic and anti-tumor effects in vivo (Folkman, 2006) significantly improved clinical and histologic signs of DSS-induced UC in MMP-9 KO mice. These results are supported by other studies showing that the potent inhibitor of angiogenesis thalidomide attenuates IBD in patients (Plamondon et al, 2007;Vasiliauskas et al, 1999) and in animal models (Prakash et al, 2008). Furthermore, deletion of thrombospondin-1 in mice, which is upregulated by endostatin (Abdollahi et al, 2004), evoked more severe experimental UC vs. WT mice (Punekar et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
“…Both drugs have been shown to be biologically effective in rats, in conditions associated with overexpression of TNF [12,13]. In order to compare the effect of TNF blockage to that of H 1 R antagonism, we also examined the effect of loratadine, a classic second generation antihistamine.…”
Section: Introductionmentioning
confidence: 99%
“…5-ASA can reduce neutrophil infiltration and formation of reactive oxygen metabolites by neutrophils [42]. Prakash et al [43] showed significant reduction of the neutrophil infiltration and mucosal inflammation after treatment of rat model of crohn's disease with salfasalazine. Lim and Hanauer [41] recorded that sulfasalazine induced significant remission compared to placebo in patients with Crohn's disease.…”
Section: Smith Et Al [28] Rutgeerts Et Al [44] Jones Et Al [45] Domentioning
confidence: 98%